O processo de aprendizagem social entre os atores do Santa Maria Tecnoparque para a promoção do desenvolvimento regional sustentável de Santa Maria/RS - Favarin, Rodrigo Reis (2019)
Sustainable Regional Development (SRD) can be seen as the application of sustainability at a local/regional level in order to consider at least economic, environmental and social aspects, and is the result of the synergy among social actors. In a context full of interactions among social actors, social learning emerges as a facilitator of the process for a more sustainable society. The Science and Technology Parks can play a critical role in exploring new opportunities and developing new ways of addressing issues related to sustainability and the environment. The Santa Maria Tecnoparque was inaugurated in the city of Santa Maria/RS with the objective of promoting the SRD of Santa Maria/RS. Thus, this dissertation aims to analyze the process of social learning among Santa Maria Tecnoparque actors for the SRD of Santa Maria/RS. In terms of methodological procedures, a descriptive-exploratory research was carried out, of a qualitative nature and that used as a strategy the case study. For the data collection, 26 interviews were conducted with four different groups of actors: Directors; Members of the Founding Institutions; Residents and Ex-Residents, documentary research and direct observation. As results, it was possible to identify that Santa Maria Tecnoparque generates benefits for the six dimensions of SRD: economic, social, environmental, political, cultural and territorial, with greater emphasis on the first two. With respect to the process of promotion of SRD of Santa Maria / RS it was possible to identify a greater number of restrictive factors in relation to the contributory factors. In the question of social learning for SRD, it was possible to identify the presence of the elements: context, participation, engagement, recognition of regional identities, reflection, negotiation, collaboration, relational practices and generated knowledge. Finally, it was possible to identify that the process of social learning for sustainability has much to contribute to the promotion of the SRD of Santa Maria/RS, by strengthening the relationships of the social actors present in the Park.